Guidelines for the management of glucocorticoids during the peri‐operative period for patients with adrenal insufficiency: Guidelines from the Association of Anaesthetists, the Royal College of Physicians and the Society for Endocrinology UK. (3rd February 2020) - Woodcock, T.; Barker, P.; Daniel, S.; Fletcher, S.; Wass, J. A. H.; Tomlinson, J. W.; Misra, U.; Dattani, M.; Arlt, W.; Vercueil, A.
Summary: These guidelines aim to ensure that patients with adrenal insufficiency are identified and adequately supplemented with glucocorticoids during the peri‐operative period. There are two major categories of adrenal insufficiency. Primary adrenal insufficiency is due to diseases of the adrenal gland (failure of the hormone‐producing gland), and secondary adrenal insufficiency is due to deficient adrenocorticotropin hormone secretion by the pituitary gland, or deficient corticotropin‐releasing hormone secretion by the hypothalamus (failure of the regulatory centres). Patients taking physiological replacement doses of corticosteroids for either primary or secondary adrenal insufficiency are at significant risk of adrenal crisis and must be given stress doses of hydrocortisone during the peri‐operative period. Many more patients other than those with adrenal and hypothalamic–pituitary causes of adrenal failure are receiving glucocorticoids as treatment for other medical conditions. Daily doses of prednisolone of 5 mg or greater in adults and 10–15 mg.m −2 hydrocortisone equivalent or greater in children may result in hypothalamo–pituitary–adrenal axis suppression if administered for 1 month or more by oral, inhaled, intranasal, intra‐articular or topical routes; this chronic administration of glucocorticoids is the most common cause of secondary adrenal suppression, sometimes referred to as tertiary adrenal insufficiency. A pragmatic approach to adrenal replacement during major stress is required; considering the evidence available, blanket recommendations would not be appropriate, and it is essential for the clinician to remember that adrenal replacement dosing following surgical stress or illness is in addition to usual steroid treatment. Patients with previously undiagnosed adrenal insufficiency sometimes present for the first time following the stress of surgery. Anaesthetists must be familiar with the symptoms and signs of acute adrenal insufficiency so that inadequate supplementation or undiagnosed adrenal insufficiency can be detected and treated promptly. Delays may prove fatal. Abstract : 권고사항 1 모든 투여 경로(경구, 흡입, 국소, 비강 내, 관절 내)로 처방 된 글루코코르티코이드 요법(성인에서 일일 prednisolone ≥ 5 mg 또는 아동에서 일일 10‐15 mg.m ‐2 hydrocorti‐ sone 해당량)은 시상하부‐뇌하수체‐부신 축의 억제를 유 발할 수 있으며, 이는 마취통증의학 전문의가 접하게 되는 부신 기능부전의 가장 흔한 원인이다. 모든 글루코코르티코이드 의존적 환자는 외과적 스트레스 또는 질병에 의한 부신위기(adrenal crisis)의 위험을 가지 며, 이러한 의학적 응급상황을 인식하고 진단할 수 있도록 준비하는 것이 필수적이다. 글루코코르티코이드의 필요성 이 의심스러운 경우, 단기 투여로 인한 장기적인 악영향이 없으므로, 이를 투여하여야 한다. 오랜 기간 지속된 부신 기능부전을 진단받은 환자는 일반 적으로 해당 질환에 대해 잘 알고 있다. 마취통증의학 전 문의는 환자의 글루코코르티코이드 자가관리 병력, 과거 모든 부신위기 에피소드와 질병, 부상, 수술 후 회복에 대 해 약물 조절을 어떻게 시행하였는지 면밀히 물어야 한다. 수술을 계획하는 경우 혹은 수술 후 환자를 치료하는 경 우, 최선의 진료를 위하여 환자의 담당 내분비전문의와 지 속적으로 협력하는 것이 중요하다. 모든 성인 부신 기능부전 환자에서 마취유도 시 hydro‐cortisone 100 mg의 정맥(i.v.) 투여가 시행되어야 하며, 이 후 환자가 평소 복용하던 경구 글루코코르티코이드 용량 의 2배를 경구로 복용할 수 있을 때까지 24시간 동안 hy‐ drocortisone 200 mg을 지속정주하여야 한다. 해당 용법 은 다른 용법들에 비하여 향상된 안전성을 보였으므로 우 선적으로 사용을 고려한다. 상기 용법은 대부분 48시간 이 내에 적절한 유지용량으로의 감량이 필요하며, 임상적 판 단에 따라 주요 또는 복잡 수술의 경우 최대 1주일까지의 사용을 고려해 볼 수 있다. 근육 내(i.m.) 투여는 정맥 주입 요법을 시행할 수 없는 상황에서 처방할 수 있다(자세한 내용은 Tables 1‐3 참조). 주요 합병증과 중대한 질병은 지속적인 스트레스 반응을 촉진하므로, 모든 글루코코르티코이드 보충요법은 이러한질환 패턴을 반영하여야 한다. Dexamethasone은 미네랄코르티코이드 활성을 가지지 않으므로 일차성 부신 기능부전 환자를 위한 글루코코르 티코이드 요법에 적합하지 않다. 부신 기능부전을 가진 아동은 혈당 조절 문제에 있어서 성 인보다 더 취약하며, 빈번한 혈당 모니터링이 필요하다. 이 들은 마취유도 시 hydrocortisone의 대량주입(bolus) 후 즉각적인 hydrocortisone의 지속정주나, 마취유도 시 대 량주입 후 4시간 간격으로 추가적인 hydrocortisone 정맥 대량주입을 하는 방법으로 치료할 수 있다. 연령과 체중에 기반한 자세한 권고사항은 본문에 기재되어 있다. 금식 기 간은 최소화되어야 하며, 부신 기능부전 환자는 정규 수술 스케줄에서 우선적으로 시행될 수 있도록 한다. 부신 기능부전 산과 환자에서 산모의 글루코코르티코이드 보충은 특별한 주의를 요한다. 여성은 임신 후기(20번째 주 부터) 동안 더 높은 유지 용량을 필요로 할 수 있는데, 진통 발생 시 hydrocortisone 100 mg을 투여하고, 이후 분만할 때까지 24시간 동안 hydrocortisone 200 mg을 지속정주 하거나 6시간 간격으로 50 mg i.m. 투여하는 용법을 사용 할 수 있다